A pharmacist-led community-based survey study: Determining the impact of the Covid-19 pandemic on actionable factors associated with worse cancer outcomes and cancer health disparities - Erika Titus-Lay; Jeffrey Nehira; Jennifer Courtney; Jacquelyn Jee; Marissa Kumar; Jenny Tiet; Vivi Le; Blythe Durbin-Johnson; Moon S. Chen, Jr; Ruth Vinall (Elsevier, 2023)
Purpose: The goals of this cross-sectional community-based survey study were to assess the impact of the Covid-19 pandemic on actionable factors which are known to contribute to worse cancer outcomes, and to determine whether race and ethnicity-based differences exist. Methods: A survey study which captured demographic information and changes in cancer outcomes-related factors since the start of the Covid-19 pandemic, was conducted at a public Covid-19 vaccination clinic over a period of 10 days during March 2021. Surveys were administered in multiple languages. Chi-square tests and ANOVA followed by post-hoc Dunnett testing assessed for race and ethnicity-based differences. Results: A total of 949 people participated (61.6% participation rate). Ninety-three surveys were removed based on inclusion criteria giving a final participant number of 856. Many participants reported postponing cancer screenings (17.8%) and cancellation of medical appointments (22.8% and 25.8% reported cancelled appointments by providers or themselves, respectively) due to the pandemic. Participants also reported decreased physical activity (44.7%) and increased tobacco and/or marijuana usage (7.0%). Conversely, participants reported consuming more fruits and vegetables (21.4%) and decreasing alcohol consumption (21.4%). Several race-related differences but no ethnicity-related differences were observed. Conclusion: Our data can be used to help guide pharmacist-led targeted outreach in our community which will help mitigate Covid-19 pandemic-driven changes in behaviors associated with worse cancer outcomes and exacerbation of cancer health disparities. To our knowledge, this is the first cancer outcomes-related study to be conducted at a public Covid-19 vaccination site and is the first pharmacist-led study in this area.